قومی بیانیہ : تصور اور لائحۂ عمل: National Narrative: Concept and Frame Work - Muhammad Zia-ul-Haq (FIKR-O NAZAR فکر ونظر, 2020)
On the directives of President of Islamic Republic of Pakistan, Islamic Research Institute was assigned the responsibility of articulation of national narrative Paigh┐m-i P┐kistan, which was launched by the President on January 16, 2018. This study is about the fundamental concepts, types, importance and strategies for articulation and preparation of a national narrative. Narrative is a powerful source for influencing the audience. It provides an alternative construction of rationality that is rooted in a particular culture and religion. National narrative, ethical narrative, episodic narrative, meta-narrative and sectarian narrative are various types of it. As per national security policy of Pakistan2014-2018 construction of a robust national narrative on extremism, sectarianism, terrorism and militancy is corner stone of an ideological response to the non-traditional threats. This national narrative is needed to be built as a strategic alternative and counter narrative to reconstruct an Islamic but tolerant society in Pakistan. It can also contribute in the changing of differences into diversity and exclusiveness into inclusiveness. Preparation and drafting of national narrative requires a comprehensive action plan and frame work. This study attempts to propose a frame work for articulation of a comprehensive national narrative.